Analisis Pengambilan Keputusan Ekonomi dalam Perspektif Ekonomi Perilaku Kahneman - Monariska, Monariska; Rizal, Vadhul; Kasril, Kasril; Danil, Muhammad; Rahayu, Evi (Economia: Journal of Economics and Management, 2025)
This study aims to analyze economic decision-making from the perspective of Behavioral Economics by referring to the ideas of Daniel Kahneman. The research employs a qualitative approach through a literature study by examining relevant academic sources. The findings indicate that economic decisions are not entirely rational but are shaped by the interaction of cognitive systems, heuristics, and cognitive biases. The dominance of intuitive thinking leads individuals to rely on mental shortcuts, which in turn produce systematic deviations in decision-making. Furthermore, through the framework of prospect theory, individuals are found to evaluate gains and losses relative to a reference point, with a stronger tendency to avoid losses than to pursue gains. These findings suggest that rationality in economic behavior is bounded and context-dependent. Therefore, integrating psychological dimensions into economic analysis is essential for a more comprehensive understanding of actual economic behavior. Abstrak Penelitian ini bertujuan menganalisis pengambilan keputusan ekonomi dalam perspektif Ekonomi Perilaku dengan merujuk pada pemikiran Daniel Kahneman. Pendekatan yang digunakan adalah kualitatif melalui studi literatur dengan mengkaji berbagai sumber akademik yang relevan. Hasil kajian menunjukkan bahwa keputusan ekonomi tidak sepenuhnya rasional, melainkan dipengaruhi oleh interaksi antara sistem kognitif, heuristik, dan bias kognitif. Dominasi proses berpikir intuitif menyebabkan individu cenderung menggunakan jalan pintas dalam mengambil keputusan, yang pada akhirnya memunculkan pola penyimpangan yang sistematis. Selain itu, melalui kerangka prospect theory, ditemukan bahwa individu mengevaluasi keuntungan dan kerugian secara relatif terhadap titik acuan tertentu, dengan kecenderungan menghindari kerugian lebih kuat dibandingkan mengejar keuntungan. Temuan ini menegaskan bahwa rasionalitas dalam ekonomi bersifat terbatas dan kontekstual. Oleh karena itu, integrasi aspek psikologis dalam analisis ekonomi menjadi penting untuk memahami perilaku ekonomi secara lebih komprehensif.